Positive definite branched continued fractions of special form - Dmytryshyn, R.I. (Carpathian Mathematical Publications, 2013)
Research of the class of branched continued fractions of special form, whose denominators do not equal to zero, is proposed and the connection of such fraction with a certain quadratic form is established. It furnishes new opportunities for the investigation of convergence of branching continued fractions of special form.